2016
DOI: 10.1007/s00268-016-3730-8
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic Blood Transfusion is Associated with Poor Perioperative and Long‐Term Outcome in Esophageal Cancer

Abstract: Allogenic blood transfusion has a significant impact on the natural course of EC after complete resection. The poor short-term and long-term outcome warrants further evaluation of the underlying molecular mechanisms induced by allogenic blood transfusion in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 42 publications
4
27
0
1
Order By: Relevance
“…This is reflected by beneficial survival data for individual indications, which were also in good agreement with data in the literature: Jarnagin et al (intrahepatic and perihilar cholangiocarcinoma, 63 and 69% [ 17 ]; Zaydfudim et al (hepatocellular carcinoma, 6059 [ 18 ]; Schiergens et al and Margonis et al (CRLM 68% with transfusion and 82% without transfusion) [ 15 , 19 ]; esophageal cancer (40% with transfusion vs. 60% without transfusion) [ 20 ]; gastric cancer (82 vs. 60%) [ 16 ]; and pancreatic cancer (50 to 60% vs. 20%) [ 13 , 21 ]. Last not least, Mörner et al showed that anemia and transfusions were associated with adverse outcome [ 22 ].…”
Section: Discussionsupporting
confidence: 84%
“…This is reflected by beneficial survival data for individual indications, which were also in good agreement with data in the literature: Jarnagin et al (intrahepatic and perihilar cholangiocarcinoma, 63 and 69% [ 17 ]; Zaydfudim et al (hepatocellular carcinoma, 6059 [ 18 ]; Schiergens et al and Margonis et al (CRLM 68% with transfusion and 82% without transfusion) [ 15 , 19 ]; esophageal cancer (40% with transfusion vs. 60% without transfusion) [ 20 ]; gastric cancer (82 vs. 60%) [ 16 ]; and pancreatic cancer (50 to 60% vs. 20%) [ 13 , 21 ]. Last not least, Mörner et al showed that anemia and transfusions were associated with adverse outcome [ 22 ].…”
Section: Discussionsupporting
confidence: 84%
“…Peri-operative blood transfusions are routinely used during cancer surgeries, however, many retrospective studies have reported increased recurrence, post-operative infection rates, and morbidity as a result of blood transfusions [ 78 , 79 , 80 ]. Gharehbaghian et al demonstrated that use of autologous salvaged blood, instead of allogenic blood for transfusion, increased the proportion of NK cell precursors and IFNγ production post-surgery [ 81 ].…”
Section: Surgical Stress Inflammation and Natural Killer Cell Dysmentioning
confidence: 99%
“…[ 3 ] Perioperative blood transfusion is also associated with cancer recurrence and metastasis. [ 13 ] Perioperative blood transfusion has been reported to increase postoperative mortality, local recurrence, and distant metastasis in patients with colorectal cancer. [ 14 ] It was also reported that blood transfusion was associated with poor prognosis in patients with esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] It was also reported that blood transfusion was associated with poor prognosis in patients with esophageal cancer. [ 13 ] One study also reported that the immunosuppressive effects of blood transfusions increased the recurrence of head and neck tumors, resulting in a poor prognosis. [ 15 ] Another study showed an association between recurrence of advanced ovarian cancer after cytoreductive surgery and perioperative allogeneic blood transfusion.…”
Section: Discussionmentioning
confidence: 99%